Development of 31P Nuclear Magnetic Resonance Methods for the Study of Phosphate Metabolisms in E. coli and B. subtilis - Dayrit, Fabian M (Archīum Ateneo, 1999)
31P NMR experiments were performed on Escherichia coli and Bacillus subtilis at various temperatures under aerobic and anaerobic conditions. The total soluble intracellular phosphate concentration was estimated to be 2 x 10^-17 mole/cell, while intracellular orthophosphate concentration was around 1 x 10^-17 mole/cell. Addition of glucose resulted in a general decrease in intracellular pH and was accompanied by the formation of sugar monophosphates. The concentrations of soluble intracellular phosphates, both inorganic and organic phosphates, were estimated by integration versus methylene diphosphonic acid (MDPA) standard. Although intracellular and extracellular orthophosphate could be observed, these appear to exchange rapidly on the NMR time scale.